Colleges and schools-College of Arts and Humanities-Music-0177
Entertaning men and soldiers of the 87th Infantry training Bn. Top Row: Eleanor Broline, MarianFranklin, LaVerne Wiley, Madaline Hyde Salinabelle Smith, Virginia McGrill, Caroline Birch, Margaret James, Catherine Segel, Lucille Ledbetter, Dorothy Cochra